TEFSIRI I PRIJEVODI KUR’ANA U XX. STOLJEĆU - Fatić, Almir (Novi Muallim, 2017)
Prikaz knjige: [Suha Taji-Farouki (ed.), Th e Qur’an and its Readers Worldwide, Contemporary Commentaries and Translations, Oxford, Oxford University Press, Qur’anic Studies Series, 2015, 600p. ISBN 978-0-19-875477-0]